Synthesis of Cu2O microcube for photochemical water decomposition - Markhabayeva, A.A.; Yerlanuly, Y.; Akhanova, N.E.; Zhakypov, A.S.; Nemkayeva, R.R.; Tulegenova, M.A.; Gabdullin, M.T. (Recent Contributions to Physics, 2023)
In this work, monovalent copper oxide (Cu2O) powders were synthesized, and studied as a material for the photochemical decomposition of water to hydrogen using sunlight. The chemical precipitation room temperature using ascorbic acid has been applied to the synthesis of powders. The production method is energy efficient, economical, fast and efficient compared to other methods. The morphology of the synthesized samples obtained by scanning electron microscopy are presented. As a result, homogeneous cubic Cu2O microparticles were obtained. An elemental composition using energy dispersive analysis is confirmed. Structural characteristics are also investigated using Raman spectroscopy and X-ray diffraction analysis. A technology for manufacturing an electrode based on synthesized powders on nickel foam was developed to study the electrochemical properties. An electrochemical characteristic as cyclic voltammetry is obtained, showing excellent redox properties. The photocatalytic properties of powders are also being studied to obtain them as photocatalysts for the decomposition of an alcohol solution in order to produce hydrogen. The photocatalytic activity of copper oxide powders for the photochemical reduction of water has been found, which makes it an interesting material for further research.